Does owning improved latrine facilities enhance the safe disposal of child feces in Africa? a systematic review and meta-analysis. - Negasa Eshete Soboksa; Beekam Kebede Olkeba; Mekonnen Birhanie Aregu (PLoS ONE)
Introduction Improved sanitation refers to those that effectively avoid human contact with excreta in a hygienic manner. Having improved latrines is a key factor in adopting safe ways of disposing of child feces. However, previous studies in Africa that examined how owning improved latrine facilities associated with household child feces disposal practices has shown inconsistent results, and no systematic review of these findings has been done. Therefore, this study aims to synthesize the evidence on the significance of households having improved latrine facilities for safe child feces disposal practices among households with under five-year-old children in Africa. Methods The searched databases include: PubMed/Medline, Ovid/Embase, ScienceDirect, AJOL and the Cochrane Library. In the search process, Google Scholar and references of other studies were considered. This review included studies that were published in English without any time restrictions. The outcome of this study was an estimate of the association between the ownership of an improved latrine and the disposal practices of children's feces. Two reviewers used the Excel data extraction tool to extract the relevant data from the studies that were included in the review. Using Stata version 16, a meta-analysis was performed with a random effects statistical model. The inverse index of variance (I2) was used to assess heterogeneity. Forest plots were used to show the pooled estimate with a 95% confidence interval. Publication bias was assessed using Egger's test and a funnel plot. Results Out of the 616 studies that were retrieved, 15 were included in the systematic review analysis and 10 were included in the meta-analysis. All studies that were included are cross-sectional studies done in Ethiopia, Nigeria, Gambia, Malawi, Eswatini, Ghana, Zambia, and a study used data from sub-Saharan Africa. Improved latrine facilities significantly enhanced the practice of safe child feces disposal, as shown by the overall effect size (OR = 2.74; 95% CI = 1.24-1.35, I2  =  99.95%). In the subgroup analysis by sample size, the presence of improved latrines significantly enhanced safe child feces disposal in studies with sample sizes less than 1000 (OR = 3.24; 95% CI = 2.86-3.62, I2  =  61.38%), while there was no significant difference in studies with sample sizes greater than 1000 (OR = 2.67; 95% CI = 0.69-4.64, I2  =  99.97%). However, studies that involved children under 5 years old indicated that improved latrine facilities significantly enhanced the practice of safe child feces disposal (OR = 4.02; 95% CI = 2.03-6.09; I2  =  99.96%). Conclusions In this research study, we examined the ownership of improved latrine facilities among households with five-year-old children to enhance the disposal of child feces in a safer manner in Africa. The high heterogeneity among the studies and the cross-sectional design of the included studies limit the causal inference and generalizability of the findings. Therefore, meta-analyses of longitudinal and experimental studies are needed to confirm the causal relationship between improved latrine facilities and safe child feces disposal practices in Africa.